1990
DOI: 10.1007/bf00334497
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin is a component of the neuritic (senile) plaque in Alzheimer dementia

Abstract: A strong immunoreactivity for ferritin was observed in the neuritic (senile) plaques in Alzheimer's disease hippocampus. The ferritin accumulation was almost exclusively associated with the microglia, which appeared to have proliferated greatly. These cells were also positive for HLA-DR, a putative marker for reactive microglia. In contrast, in the diffuse plaques, which were without neuritic pathology, the ferritin-stained microglia appeared to be normal. Microglia were seen frequently in contact with neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
1
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(139 citation statements)
references
References 29 publications
7
129
1
2
Order By: Relevance
“…Similar patterns have been described in studies of AD transgenic mice and postmortem human AD cases, and were attributed to the presence of amyloid plaques using histological confirmation [11][12][13][14][15][16][17][18][19]. It has been proposed that the visualization on MRI of plaques in humans and mice is based on the fact that these deposits colocalize with iron, which gives rise to magnetic susceptibility effects on T2*-weighted images over volumes that are much larger than the actual size of amyloid plaques [17,[19][20][21][22][23][24]. An alternative method to measure these susceptibility changes in the brain is to measure the relative phase in regions of interest (ROIs), because it has been shown that this is a reliable indicator of the iron content in the brain [25][26][27][28].…”
Section: Introductionsupporting
confidence: 59%
“…Similar patterns have been described in studies of AD transgenic mice and postmortem human AD cases, and were attributed to the presence of amyloid plaques using histological confirmation [11][12][13][14][15][16][17][18][19]. It has been proposed that the visualization on MRI of plaques in humans and mice is based on the fact that these deposits colocalize with iron, which gives rise to magnetic susceptibility effects on T2*-weighted images over volumes that are much larger than the actual size of amyloid plaques [17,[19][20][21][22][23][24]. An alternative method to measure these susceptibility changes in the brain is to measure the relative phase in regions of interest (ROIs), because it has been shown that this is a reliable indicator of the iron content in the brain [25][26][27][28].…”
Section: Introductionsupporting
confidence: 59%
“…82 The presence of ferritin in the senile plaque, has also been proposed as evidence for a role for free radicals in amyloid formation. 83 There is less evidence for a relation between AD and chronic low level hyperexcitatory events. However a correlation of extended dietary ingestion of a glutaminergic agonist, 13-methylamino-L-alanine, with a delayed occurrence of a neurological complex (Amyotrophic Lateral Sclerosis-Parkinsonism-Dementia) has been claimed.…”
Section: Aging and Alzheimer's Diseasementioning
confidence: 99%
“…Thus, although the presence of increased aluminum in AD brain is generally confirmed, in one recent report its presence in AD (senile) plaques has been attributed to experimental artifact (50). Similarly, the presence of an increased concentration of ferritin in AD brain reported earlier (31,33) and its localization in neuritic plaques of AD patients (51) has been conVolume 102, Supplement 3, September 1994 211 firmed, but its association with Al was not seen in several AD brains (33). Most reports show that familial cases of AD once considered due to genetic mutations in the AD-gene in chromosome 21 may also arise from mutations in chromosomes 19 and 14 (52).…”
Section: Role Of Iron In Plaque Formationmentioning
confidence: 83%